2009
DOI: 10.1111/j.1462-2920.2009.01920.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages drive strain diversification in a marine Flavobacterium: implications for phage resistance and physiological properties

Abstract: Genetic, structural and physiological differences between strains of the marine bacterium Cellulophaga baltica MM#3 (Flavobacteriaceae) developing in response to the activity of two virulent bacteriophages, Phi S(M) and Phi S(T), was investigated during 3 weeks incubation in chemostat cultures. A distinct strain succession towards increased phage resistance and a diversification of the metabolic properties was observed. During the incubation the bacterial population diversified from a single strain, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 42 publications
2
96
0
2
Order By: Relevance
“…Rapid evolution of resistant microbial strains and their viral predators is part of the perpetual arms race referred to as Red Queen dynamics. These evolutionary changes are routinely observed in chemostat studies (Bohannan and Lenski, 2002;Lennon and Martiny, 2008;Middelboe et al, 2009) and in environmental surveys (Vos et al, 2009). Our results do not distinguish between variation due to selection acting on pre-existing diversity or de novo generation of mutants.…”
Section: Fine-grained Analyses Of Microbial Strains and Viral Genotypesmentioning
confidence: 49%
“…Rapid evolution of resistant microbial strains and their viral predators is part of the perpetual arms race referred to as Red Queen dynamics. These evolutionary changes are routinely observed in chemostat studies (Bohannan and Lenski, 2002;Lennon and Martiny, 2008;Middelboe et al, 2009) and in environmental surveys (Vos et al, 2009). Our results do not distinguish between variation due to selection acting on pre-existing diversity or de novo generation of mutants.…”
Section: Fine-grained Analyses Of Microbial Strains and Viral Genotypesmentioning
confidence: 49%
“…Selection for viral resistance is known to alter nutrient acquisition rates in marine bacteria (27,41), and in laboratory experiments, the fraction of Synechococcus cells that are resistant to co-occurring cyanophages influences nutrient turnover rates (46). Taken together, this evidence suggests that rapid coevolutionary processes may influence how viruses mediate nutrient cycling in the ocean.…”
Section: Discussionmentioning
confidence: 69%
“…Phages have previously been shown to be important drivers of bacterial diversification at the strain level by selecting for phageresistant strains, thus leading to a local arms race and co-evolution between phage and host populations (Middelboe et al, 2009). Hence, the versatility within the species is prompted by the exchange of genetic material as it has been proposed for the Roseobacter clade (Newton et al, 2010) and is not associated with any oceanographic parameters, which has been confirmed by the analysis of the TARA data (Supplementary Table S6).…”
Section: Discussionmentioning
confidence: 99%